2021
DOI: 10.26599/jnr.2021.9040011
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of clinical cell therapy for patients with vascular dementia

Abstract: Background:Vascular dementia (VD) is a series of clinical and neurophysiological manifestations caused by cerebrovascular disease. As the human lifespan increases, the number of people affected by age-related dementia is growing at an alarming pace, but no proved therapeutic methods can stop it from getting worse.Objective:To investigate the neurorestorative effects of injecting olfactory ensheathing cells (OECs), Schwann cells (SCs), and olfactory receptor neurons (ORNs) into olfactory sub-mucosa in VD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Wang et al. transplanted olfactory neurons (ONs) in a patient with vascular dementia (VD), who improved damaged neurological and psychological behavior by assessing Mini-Mental Status Examination (MMSE), Montreal Cognitive Assessment (MoCA) and Clinical Dementia Rating (CDR) [ 9 ]. Guo et al.…”
Section: Classification and Clinical Therapeutic Results Of The Main ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al. transplanted olfactory neurons (ONs) in a patient with vascular dementia (VD), who improved damaged neurological and psychological behavior by assessing Mini-Mental Status Examination (MMSE), Montreal Cognitive Assessment (MoCA) and Clinical Dementia Rating (CDR) [ 9 ]. Guo et al.…”
Section: Classification and Clinical Therapeutic Results Of The Main ...mentioning
confidence: 99%
“…After being transplanted, they seem to migrate where they are needed, and become local functional neurons as they need to be compensated or replaced [ 114 ]; so the indications of human olfactory neuron therapy should be neurological diseases in which many neurons are lost or die and neurological functions are impaired, such as dementia, PD, etc. Pilot clinical studies demonstrated that patients with PD and VD got benefits from the human olfactory neuron therapy [ 9 , 10 ]. The prospect of the human olfactory neuron therapy is promising, but needs to be proved by multicenter, randomized, double blind, placebo-controlled clinical trials.…”
Section: Indications and The Prospect Of Cell Therapies For Neurologi...mentioning
confidence: 99%
“…It also confers the ability to phosphorylate IRF3 by TBK1, thus completing the recruitment of TBK1 and IRF3 ( 35 ). Subsequently Type I IFN, which has an activating effect on the immune system ( 36 , 37 ), is produced and exerts direct and indirect antitumor effects by promoting the production of perforin and granzyme by CTL and NK cells ( 10 , 38 , 39 ).…”
Section: Dna Damage Repair Is Related To Innate Immunity and Tumor Immune Escapementioning
confidence: 99%
“…Meanwhile, neurorestorative treatment have also emerged in recent years and have been shown to repair the function of damaged nerves in some sense ( 9 ). For example, olfactory ensheathing cells, with their superior ability to integrate and repair nerves ( 10 , 11 ), interact with glial scars to stimulate vascular and axonal growth ( 12 ), in order to repair brain nerves after tumor damage and help restore brain function ( 13 ). In contrast to these rapid developments, immunotherapy, which has achieved superior therapeutic results in other tumors, remains ineffective in brain tumors.…”
Section: Introductionmentioning
confidence: 99%